Tree ring δ¹³C of Pines at acidic soil forest in central Vietnam: A preliminary result for further stable isotope application on climate change and environmental protection - Dinh Viet, Hung; Nguyen Thanh Kim, Hue; -Tien Chu, Trung (Vietnam Journal of Earth Sciences, 2025)
This case study evaluates an innovative methodological approach that integrates soil chemical analysis (including pH, organic matter, total nitrogen, and grain size composition) with tree-ring δ¹³C measurements to assess long-term forest soil acidification processes. The study was conducted in Nang Pine Forest, located in Phong Nha - Ke Bang National Park, central Vietnam. Soil grain size analysis reveals a predominance of fine particles over coarse particles. There is a difference in the distribution of soil components at depth. The results indicate that the soil tends to be acidic, with a low pH that increases in depth, while it contrasts with the total nitrogen content. This acidity may result from natural processes and human activities, such as the release of acid rain. The findings also highlight the influence of topography and climate on soil properties.Furthermore, soil pH was negatively correlated with δ¹³C in pine tree rings in central Vietnam. This relationship could serve as a valuable tool for assessing past soil degradation processes, reconstructing historical environmental changes, or analyzing the connection between δ¹³C content in pine tree rings and climate change in the region. The results suggest that mitigating soil acidity and supporting healthier tree growth are essential to improve soil pH through the planting of suitable tree species and effective vegetation management in the study area. This study's integrated approach provides both current assessments and historical reconstructions, establishing a replicable and cost-effective methodological framework applicable to other tropical forest ecosystems under acidification stress. This framework provides valuable insights to advance both research and conservation management.